Methylglyoxal-Modified Human Serum Albumin Binds to Leukocyte Myeloperoxidase and Inhibits its Enzymatic Activity - Oleg M. Panasenko; Viktor A. Ivanov; Elena V. Mikhalchik; Irina V. Gorudko; Daria V. Grigorieva; Liliya Yu. Basyreva; Ekaterina V. Shmeleva; Sergey A. Gusev; Valeria A. Kostevich; Nikolay P. Gorbunov; Alexey V. Sokolov (MDPI AG, 2022)
Hyperglycemia in diabetes mellitus induces modification of proteins by glucose and its derivative methylglyoxal (MG). Neutrophils perform their bactericidal activity mainly via reactive halogen (RHS) and oxygen (ROS) species generation catalyzed by myeloperoxidase (MPO) stored in neutrophil azurophilic granules (AGs) and membrane NADPH oxidase, respectively. Herein, we study the binding of human serum albumin (HSA) modified with MG (HSA-MG) to MPO and its effects on MPO activity and release by neutrophils. Peroxidase activity of MPO was registered by oxidation of 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, and chlorinating activity by decolorization of Celestine blue B dye. Binding of HSA-MG to MPO was studied by affinity chromatography, disc-electrophoresis, ligand Western blotting and enzyme-linked solid phase immunoassay using monoclonal antibodies (mAbs) to MPO. ROS and RHS generation were detected by lucigenin (Luc) and luminol (Lum) chemiluminescence (CL), respectively. Neutrophil degranulation was assessed by flow cytometry using fluorescent labeled antibodies to the marker proteins CD63 from AGs and CD11b from peroxidase-negative granules (PNGs). NETosis was assayed by quantifying DNA network-like structures (NET-like structures) in blood smears stained by Romanowsky. HSA-MG bound to MPO, giving a stable complex (Kd = 1.5 nM) and competing with mAbs, and non-competitively inhibited peroxidase and chlorinating MPO activity and induced degranulation of PNGs but not of AGs. HSA-MG enhanced Luc-CL per se or following PMA, unlike Lum-CL, and did not affect spontaneous or PMA-stimulated NETosis. Thus, HSA modified under hyperglycemia-like conditions stimulated NADPH oxidase of neutrophils but dampened their functions dependent on activity of MPO, with no effect on its release via degranulation or NETosis. This phenomenon could underlie the downregulation of bactericidal activity of MPO and neutrophils, and hence of innate immunity, giving rise to wound healing impairment and susceptibility to infection in patients with hyperglycemia.